Mastering space : hegemony, territory and international political economy - Agnew, John A., 1949-; Corbridge, Stuart, 1957- (London ; New York : Routledge, 1995)
For two hundred years, the domination of some countries by others has been intrinsic to international relations, with national economic and political strength viewed as essential to a nation's survival and global position. Mastering Space maps paths out of the tangle of international relations by identifying the essential features of this "state-centredness" and suggests an optimistic alternative more in keeping with the contemporary post-Cold War climate. Drawing on recent geopolitical thinking, the authors claim that the dynamism of the international political economy has been obscured by excessive attention on the state as an unchanging actor. Dealing with such topical issues as Japan's rise to economic dominance and the US's perceived decline, as well as the global impact of continued geographical change, the book discusses the role of geographical organization in the global political economy and the impact of increasing economic globalization and political fragmentation in future international relations. The authors identify the present time as crucial to the global political economy, and explore the possibilities of moving the world from mastering space to real reciprocity between people and places -- from the publisher
Includes bibliographical references (p. 228-249) and index.
Keywords: Geopolitics; World politics; International relations; International economic relations